Review article: The Role of Probiotic Strains in Cancer Prevention: Probiotic strains: Key in Cancer Prevention - Mokhtar Jawad Al-Imam; Faisal, Anwer; Ahmed Majeed Al-Shammari (Iraqi Journal of Cancer and Medical Genetics, 2024)
Probiotics are living microorganisms that confer health benefits when administered in adequate amounts. One main way that probiotics may help fight cancer is by changing bacteria in the gut. Some types of probiotics have been shown to stop the growth of harmful bacteria, make chemicals that stop cancer cells from spreading, and boost the production of short-chain fatty acids that fight inflammation and cell growth. Probiotics may also strengthen the intestinal epithelial barrier, stopping the movement of compounds that can cause cancer and stopping chronic inflammation, which is known to increase the risk of cancer. Probiotics can also change the way your immune system works. For example, some types can make natural killer cells, dendritic cells, and T cells work harder, which is very important for finding and killing cancer. Some probiotics have also been shown to lower oxidative stress and DNA damage. This makes it less likely that genetic changes that can cause cancer will occur. Although more research needs to be done on how probiotics can help prevent cancer, several clinical studies have shown encouraging results, especially when it comes to colorectal cancer. The burgeoning field of probiotics and cancer prevention holds potential for transforming our understanding of the role of the gut microbiome in cancer development and progression. Continued research is essential to optimize the use of probiotics as a complementary approach to cancer prevention and treatment.